2019
DOI: 10.1016/j.jbo.2019.100237
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of Semaphorin 4D are decreased by adjuvant tamoxifen but not aromatase inhibitor therapy in breast cancer patients

Abstract: Background Semaphorin 4D (Sema4D) is a glycoprotein that inhibits bone formation and has been associated with cancer progression and the occurrence of bone metastases. Recently, Sema4D expression has been linked to estrogen signaling in breast cancer. Endocrine therapies like tamoxifen and aromatase inhibitors (AI) are a standard therapeutic approach in hormone receptor positive breast cancers. Tamoxifen exerts ER-agonistic effects on bone, whereas AI negatively affect bone health by increasing re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A 150-kDa glycoprotein transmembrane homodimer, Sema4D (CD100) - a member of the Semaphorin family - is a signaling protein implicated in axon-guiding processes. Recent data, however, suggest that Sema4D has additional functions, including immunomodulatory activity, platelet inactivation, angiogenic stimulation, and modulation of bone formation ( 5 , 12 , 13 ). The coupling factor Sema4D, expressed by osteoclast, has been proposed as a novel target for treating osteoporosis ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…A 150-kDa glycoprotein transmembrane homodimer, Sema4D (CD100) - a member of the Semaphorin family - is a signaling protein implicated in axon-guiding processes. Recent data, however, suggest that Sema4D has additional functions, including immunomodulatory activity, platelet inactivation, angiogenic stimulation, and modulation of bone formation ( 5 , 12 , 13 ). The coupling factor Sema4D, expressed by osteoclast, has been proposed as a novel target for treating osteoporosis ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sema4D is associated with the etiology of various types of cancer. 88,89 Roles for Sema4D have been demonstrated in breast cancer, [90][91][92][93][94][95][96][97][98][99][100][101] colorectal carcer, [102][103][104][105][106][107][108] gastric cancer, 109 esophageal cancer, 110,111 lung cancer, [112][113][114] pancreatic cancer, 107,[115][116][117] cholangiocarcinoma, 118 prostatic cancer, [119][120][121][122][123] bladder cancer, 124,125 kidney cancer, 125 cervical cancer, 126 ovarian cancer, [127][128][129][130] malignant melanoma, 131 osteosarcoma, 132 head-and-neck cancer,…”
Section: Sema4d In Cancermentioning
confidence: 99%
“…Sema4D is associated with the etiology of various types of cancer 88,89 . Roles for Sema4D have been demonstrated in breast cancer, 90–101 colorectal carcer, 102–108 gastric cancer, 109 esophageal cancer, 110,111 lung cancer, 112–114 pancreatic cancer, 107,115–117 cholangiocarcinoma, 118 prostatic cancer, 119–123 bladder cancer, 124,125 kidney cancer, 125 cervical cancer, 126 ovarian cancer, 127–130 malignant melanoma, 131 osteosarcoma, 132 head‐and‐neck cancer, 133–137 medulloblastoma, 138 leukemia, 139–143 malignant lymphoma, 144 and multiple myeloma (Figure 4). 145 Cancer cells express Sema4D or its receptor, which are typically up‐ or down‐regulated in tumors compared to normal tissues.…”
Section: Semaphorins In Pathogenesismentioning
confidence: 99%
“…In bone homeostasis, Sema4D has an osteoblast-inhibitor activity and it is normally produced by osteoclasts 40 ; however, in metastatic lesions a locally increased concentration of Sema4D can promote osteolysis. Notably, it was reported that breast cancer patients treated with the anti-hormonal drug tamoxifen have reduced plasmatic levels of Sema4D 41 , an effect which could potentially account for some of the reported bone-protective effects of this drug. The same mechanism was not observed in response to another class of hormonal drugs, the aromatase inhibitors (AI), which may further negatively affect bone mass due to deprivation of bone protective estrogens.…”
Section: Semaphorins As Clinical Biomarkers In Human Cancersmentioning
confidence: 99%